Transfer semi-hydrogenation of terminal alkynes with a well-defined iron complex - Chowdhury, Deep; Goswami, Souvik; Krishna, Gamidi Rama; Mukherjee, Arup (Dalton Transaction, 2024)
The synthesis and characterization of a bis-iron(ii) complex was accomplished upon treatment of a phosphine free NNN-pincer ligand (L) with FeCl2 center dot 4H2O under ambient conditions. The deep greenish colored iron(ii) complex (Fe-1) was characterized by a single-crystal X-ray diffraction study along with IR spectroscopy, UV-Vis spectroscopy, mass spectrometry, and elemental analysis. The Fe-1 complex was tested for the transfer semi-hydrogenation of terminal alkynes to the corresponding alkenes through the dehydrogenation of dimethyl amine-borane. This procedure enables the conversion of various structurally different terminal alkynes to alkenes under mild conditions. Control experiments were performed to shed light on the possible intermediates generated during the present protocol. A bench stable iron(ii) complex with the pincer ligand backbone was synthesized and characterized. The well-defined iron complex was successfully utilized for the dehydrogenation of DMAB and subsequent transfer semi-hydrogenation of terminal alkynes.

Unraveling the metal-ligand cooperativity in a phosphine-free Mn(II)-catalyzed transfer hydrogenation of nitriles to primary amines and dehydrogenation of dimethylamine borane - Chowdhury, Deep; Gupta, Kriti; Gamidi, Rama Krishna; Jindal, Garima; Mukherjee, Arup (ACS CATALYSIS, 2024)
Keywords: CATALYZED TRANSFER HYDROGENATION; STEREOSELECTIVE TRANSFER SEMIHYDROGENATION